DISAIN SISTEM INFORMASI CUSTOMER RELATIONSHIP MANAGEMENT PADA KLUB ADE RAI WISMA GADING PERMAI - Joko Susilo (Institut Bisnis dan Informatika Kwik Kian Gie, 2015)
The development of information and communication technology is very fast nowadays be a trigger factor many companies that want to compete effectively for implementing information and communication technology within the organization to support the performance and achievement of corporate goals. With a vision to be one of the best fitness center in Jakarta, even in Indonesia, Klub Ade Rai Wisma Gading Permai need to use information and communication technology to support business processes in order to manage the relationship with the customer. But this time the company does not have information technology systems that can assist the management in generating information related to the customer making it difficult for the management to make a strategic decision of the company. The method used in this study were interviews and observations at Klub Ade Rai Wisma Gading Permai. Development system used in this study is the system development life cycle that can be described with the use of zero diagrams, context diagrams, and detailed diagrams. The results of this research are Customer Relationship Management information system that can assist companies in managing customer data, receiving complaints and suggestions, the reward system, extend the period of active members, and reports to manage relationships with customers, so the company may be better in efforts to build and manage relationships with customers. The conclusion of this study indicate that human resource information system to easily manage employee data and generate the reports needed.Â Key words: information systems, Customer Relationship Management, Fitness Centre.